Reconciling the European registered capital regime with a modern corporate reorganization law: Experience from the Czech insolvency law reform - Tomáš Richter (Charles University in Prague, Institute of Economic Studies (IES), 2009)
In this article, I deal with the apparent conflict between certain provisions of the Second Company Law Directive, in particular its Article 25 regulating increases of the share capital of European joint-stock companies, and basic logic of non-liquidation insolvency proceedings, usually referred to as reorganization. Using the ECJ case law on the Directive, I conclude that although on its face the Directive seems to presents a serious obstacle for national legislators wishing to provide their companies with economically sound reorganization law, that appearance is incorrect and the Directive's rules on changes of share capital do not present an insurmountable hurdle to the adoption of rational corporate insolvency law. As a side note, I also mention the Prospectus Directive and its disclosure requirements. The results of that review turn out less up-beat and I conclude by suggesting that the European legislator revisits and amends that Directive so that it does not present an unnecessary administrative burden on reorganizing European companies.
Keywords: G33; K22; 330; bankruptcy; insolvency; reorganization; registered share capital; European company law; Second Company Law Directive; Czech law; absolute priority; pre-emptive rights; Prospectus Directive; Insolvenz; Insolvenz; Gesellschaftsrecht; EU-Recht; Tschechoslowakei